Symbolism of Redemption and Repentance in Meursault's Trajectory: A Christian Interpretation of Albert Camus's “L'Étranger” (The Outsider) - AGWU, Peter Akongfeh; ASHABUA, Derick A. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The Outsider, known in French as “L'Étranger” has intrigued literary scholars with its existential themes, yet a comprehensive perspective of theological symbolism, particularly pertaining to redemption and repentance in the protagonist, Meursault's trajectory remains largely unexplored. This study fill this gap by examining the sophisticated viewpoints of Christian imagery embedded in Meursault's character and actions. The primary objective is to analyze and interpret the symbolic elements of redemption and repentance in Meursault's journey drawing on the broader framework of Christian themes. This research adopts a hermeneutic approach, to employ principles of literary analysis and Christian symbolism interpretation. Drawing on relevant theological frameworks, the study aims to decipher the Christian undertones in Meursault's path, and to explore how the character's experiences align with or subvert these traditional Christian narratives. The study’s findings reveals the complicated levels of Christian symbolism throughout Meursault's journey. Elements such as his moral struggles, moments of self-reflection, and interactions with other characters are examined to unveil the symbolic significance of these biblical concepts. The analysis highlights the novel's potential dualities in existential and Christian themes. The research’s contribution to existing knowledge is that it offers a fresh perspective on Albert Camus's literary creations.